2019
DOI: 10.5430/rwe.v10n2p108
|View full text |Cite
|
Sign up to set email alerts
|

Scrutinising the Socio-Demographic Pattern of Parenting Practices and Parenting Styles in Upholding Child’s Protection and Privacy to Address Paedophilia Issue

Abstract: Paedophilia issue has become a global issue around the world, including Malaysia. In today's era of globalisation and modernisation, the seriousness of paedophilia issue is undeniable. As the closest persons to children, parents have been recognised as the critical actor that contributes to children's protection and security. However, research related to "parenting practices" and "parenting styles" specifically to address the paedophilia issue remains limited in Malaysian context. Thus, a doctoral research, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The MCMC reported that 61.8% of them shared content online with the following purposes 3 above shows that sharing of information online is for well-intended reasons including for a good cause such as raising awareness about an issue. It can also be said that parents sharing information about their children without the intention or knowledge that the information or images of their children become easy targets to be used inappropriately and uploaded on pornographic websites (Hamid et al, 2019). A chat group with hundred members indecently discussing a screenshot about a prepubescent girl dressed in a swimming costume is an alarming fact that parents are unaware that they are contributing photos of their children online for illicit purposes (Moh, 2016).…”
Section: Sharing Of Online Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…The MCMC reported that 61.8% of them shared content online with the following purposes 3 above shows that sharing of information online is for well-intended reasons including for a good cause such as raising awareness about an issue. It can also be said that parents sharing information about their children without the intention or knowledge that the information or images of their children become easy targets to be used inappropriately and uploaded on pornographic websites (Hamid et al, 2019). A chat group with hundred members indecently discussing a screenshot about a prepubescent girl dressed in a swimming costume is an alarming fact that parents are unaware that they are contributing photos of their children online for illicit purposes (Moh, 2016).…”
Section: Sharing Of Online Informationmentioning
confidence: 99%
“…Parents or legal guardians are primarily accountable for the upbringing and development of a child (Hamid et al, 2020), and mainly a concern for the best interest of the child as entrenched under the UN Convention on the Rights of the Child (CRC) 1989. The CRC was adopted by the Malaysian Government in 1995 with some reservations.…”
Section: Parental Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…(MacPherson, 1989). One of the duties and responsibilities of parents is to protect their children's privacy (Abd Hamid et al, 2019). Privacy gives children and adolescents the opportunity to learn about gender characteristics, and understand and accept gender roles (Diler, 2014).…”
mentioning
confidence: 99%
“…Privacy gives children and adolescents the opportunity to learn about gender characteristics, and understand and accept gender roles (Diler, 2014). Problems in privacy education are seen as an important factor that may lead to abuse cases (Gunes, 2017;Abd Hamid et al, 2019). Research shows that children of different ages have different understandings and needs regarding privacy, and findings have indicated that children do not have a clear understanding of privacy (Livingstone et al, 2019;Byrne et al, 2016;Chaudron et al, 2018).…”
mentioning
confidence: 99%